A Bre1-associated Protein, Large 1 (Lge1), Promotes H2B Ubiquitylation during the Early Stages of Transcription Elongation - Song, Young-Ha (American Society for Biochemistry and Molecular Biology, 2010)
Transcription activation has been proposed to require both ubiquitylation and deubiquitylation of histone H2B. Here, we show that Lge1 (Large 1) is found in a complex containing Rad6·Bre1 and that it controls the recruitment of Bre1, a ubiquitin ligase, and Ubp8, a deubiquitylase, to promote ubiquitylation during the early steps in elongation. Chromatin immunoprecipitation experiments showed that Lge1 associates with promoter and coding regions of actively transcribed genes in a transcription-dependent manner. Disruption of Lge1 abolished ubiquitylation of histone H2B on lysine 123 and H3 methylation on lysines 4 and 79 and resulted in significant sensitivity to 6-azauracil and mycophenolic acid. In particular, in Lge1-deficient cells, Bre1 recruitment was attenuated, whereas recruitment of Ubp8 was facilitated. These alterations were coincident with changes in the interaction between Bre1·Ubp8 and RNA polymerase II phosphorylated at serine 5 of the C-terminal domain. We propose that Lge1 has a novel function in disrupting the balance between the recruitment of Bre1 and Ubp8, thus promoting transcription elongation.